Reintegration of disabled workers to labor market. A stochastic analysis based on the continuous sample of working lives - Vilà Prats, Víctor; Moreno-Ruiz, Rafael; Trigo-Martínez, Eduardo; Gómez-Pérez-Cacho, Olga (My University, 2022)
The public social security system provides a wide range of benefits. The different contingencies for which it provides coverage provide security for those exposed. However, in order to determine the objectivity of the amount of benefits, it is necessary to analyse the risk factors involved. Total Permanent Disability (TPD) provides protection for people who are unable to carry out their usual profession due to reduced functionality. The compatibility of this benefit with a job other than the usual one prior to the occurrence of the contingency raises doubts about the objectivity and fairness of the benefit, which is due to the complexity and variety of situations in which the subject may find himself. This paper questions the current differentiation in the amount of the benefit and demonstrates the consequences of using a simple system to measure a complex risk, showing that the variables of sex, age or years of incapacity are factors that have a significant influence on it, and should therefore be used to guarantee an equitable and fair system of protection.
Keywords: Mercado de trabajo; Seguridad social; Política social; Pensiones; Enfermedades profesionales; Total Permanent Disability; Risk Factors; Equitable Protection